ТЕНДЕНЦИИ НА ЛУДИЗАМ И ПРАГМАТИЗАМ ВО МАКЕДОНСКАТА ПРОЗА (Филолошки студии, 2019)
This paper shows the importance of two tendencies in contemporary literature in Macedonia: emphasizing the literary game and accomplishing literary communication. Its theoretic position of analyzing two principles of literature (its ludicity and its pragmatics) as its main principles, is illustrated with two examples from the recent prose production: the novel A Conversation with Spinosa (2002) by Goce Smilevski and the stories by Olivera Korveziroska The knitted stories (2003). In this two books can be seen the postmodern manners, such as the mystification, intertextuality, “disappearing of the author”, citation etc. All those postmodern signs are comment in correlation with another prose writings, especially from the Slavonic literatures. That gives to this research the special comparative dimension. For example, in the case of stories by Korveziroska there are some analyses of concrete intertextual contacts between her writings and some writings by contemporary Serbian writer Vladislav Bajac. In this way, the touches between cultures are discussed through the close interferings between two or more works from different Slavonic literatures.